Toradora!. Vol. 5 - Takemiya, Yuyuko, 1978- (Seven Seas Entertainment, 2019)
"As fall draws to a close, the looming Cultural Festival already has everyone descending into stress and squabbling when a new threat looms- a sudden appearance from Taiga's father! Can Ryuuji help the volatile Palmtop Tiger deal with her deadbeat dad, or will this new tension split them even further apart? And what happens if reconciling Taiga with her dad means losing her as a neighbor?"--Cover, page 4.